THE CONTEMPORARY MAGISTERIUM ON POVERTY - Mruma, Wilhelmina Tunu (Asian Horizons, 2017)
Care for the poor is a mission which God has entrusted to us. As Christians, we have been singled out for this special mission of love for and service to the poor. Serving the poor entails creating awareness to them of knowing that they belong to the community. The aspect of sense of belonging is important for the poor as they have a danger of not knowing that they are part of the community. It is for this reason that this article deals with the understanding of poverty in the contemporary magisterium. Poverty is a condition which triggers the minds of the community members in every society that they have a duty to build interest to know, love and serve the poor. Knowing, loving and serving the poor consists of creating a fair and equal society in which everyone matters, making the rights of the poor recognized and protected, hence, promoting peaceful coexistence within and among people. The magisterium, as explained in this article, reminds us that everyone counts and all people ought to be given fair and equal opportunity regardless of status, culture, gender, religion, age or race.